Benzyl-Type Cation Initiated Nucleophilic Substitution on Furan and Thiophene by Using α-EWG Ketene S,S-Acetals as Nucleophiles - Sun, Shaoguang; Liu, Jun; Liu, Qun; Wang, Mang (Synthesis, 2012)
An efficient method for introducing nucleophiles on furan and thiophene has been established via the in situ formation of benzyl-type carbocation, delocalization of the carbocation on heterocyclic ring, and nucleophilic trap of α-EWG ketene S,S-acetal sequence at the 5-position.
Keywords: alcohols; carbocation; catalysis; nucleophiles; titanium